Pengembangan Mobilitas dan Sensor pada Robot Pemetik Buah Stroberi - Fahrun Maulana, Ahmad; Putri; Ka’ka, Simon; Paisal (Politeknik Negeri Ujung Pandang, 2026)
This research aims to develop the mobility and sensor systems of a strawberry-picking robot so that it can move stably in garden areas and harvest fruit without causing damage. The research method includes the design of the mechanical structure, assembly of an electronic system based on Raspberry Pi and Arduino Uno, and programming of strawberry ripeness detection using the You Only Look Once (YOLOv8) algorithm. The robot is designed with four wheels driven by DC motors, a manipulator equipped with a servo motor, and a distance sensor to maintain the position of the end-effector relative to the fruit. The test results show that the YOLOv8-based detection system is capable of identifying the ripeness level of strawberries with consistent accuracy. The manipulator can adjust its position relative to the fruit and perform automatic picking. The mobility system demonstrates stable movement on uneven terrain and is able to stop automatically when a ripe fruit is detected. The integration between the detection system, manipulator control, and drive system operates in real time, although there is still a slight delay due to the processing limitations of the Raspberry Pi 5. It can be concluded that the development of mobility and sensor systems in the strawberry-picking robot can improve the effectiveness of automated harvesting, minimize fruit damage, and support efficiency in agricultural production.